The FSH-inhibin axis in prader-willi syndrome: heterogeneity of gonadal dysfunction - Gross-Tsur Varda; Hirsch Harry J; Benarroch Fortu; Eldar-Geva Talia (BMC, 2012)
Abstract Background We characterized the spectrum and etiology of hypogonadism in a cohort of Prader-Willi syndrome (PWS) adolescents and adults. Methods Reproductive hormonal profiles and physical examination were performed on 19 males and 16 females ages 16-34 years with PWS. Gonadotropins, sex-steroids, inhibin B (INB) and anti-Mullerian hormone (AMH) were measured. We defined 4 groups according to the relative contribution of central and gonadal dysfunction based on FSH and INB levels: Group A: primary hypogonadism (FSH >15 IU/l and undetectable INB (<10 pg/ml); Group B: central hypogonadism (FSH <0.5 IU/l, INB <10 pg/ml); Group C: partial gonadal & central dysfunction (FSH 1.5-15 IU/l, INB >20 pg/ml); Group D: mild central and severe gonadal dysfunction (FSH 1.5-15 IU/l, INB < 10 pg/ml. Results There were 10, 8, 9 and 8 individuals in Groups A-D respectively; significantly more males in group A (9, 4, 4 and 2; P = 0.04). Significant differences between the groups were found in mean testosterone (P = 0.04), AMH (P = 0.003) and pubic hair (P = 0.04) in males and mean LH (P = 0.003) and breast development (P = 0.04) in females. Mean age, height, weight, BMI and the distribution of genetic subtypes were similar within the groups. Conclusions Analysis of FSH and inhibin B revealed four distinct phenotypes ranging from primary gonadal to central hypogonadism. Primary gonadal dysfunction was common, while severe gonadotropin deficiency was rare. Longitudinal studies are needed to verify whether the individual phenotypes are consistent.